Strategi Pembelajaran Teaching Motivating pada Mata Pelajaran Pendidikan Agama Islam pada Masa Covid-19 - Anita Pronika (Medan Resource Center, 2022)
Teaching Motivation is an important role for teachers in carrying out the teaching and learning process for their students, in this study more emphasis on teaching motivational learning strategies in Islamic Religious Education subjects during the Covid-19 period. The impact that occurs with the Covid-19, namely the learning process is no longer in class but by using the Google Meet and Zoom applications. Teachers motivate and students are motivated to learn. Motivation has an important function in learning, because motivation will determine the identity of the learning efforts carried out by students, motivation is by encouraging students to act, guiding the direction of action, selecting actions. Some learning strategies that can be used by teachers to motivate their students in the learning process are by: using a variety of methods and activities, making students active participants, making assignments that are challenging but realistic and appropriate, creating a conducive class atmosphere that is not stressful, giving assignments professionally, involve yourself in helping students achieve results, instruct students to be successful in learning, avoid interpersonal competence, provide input, value success and example, be enthusiastic in teaching, set high but realistic standards for all students, giving rewards to motivate, create activities and involve all students in the class, avoid bad comments, identify students' interests, and care about students during the teaching and learning process.